2021
DOI: 10.1155/2021/7216339
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel GCK and HNF4α Gene Variants in Japanese Pediatric Patients with Onset of Diabetes before 17 Years of Age

Abstract: Background. Maturity-onset diabetes of the young (MODY) is commonly misdiagnosed as type 1 or type 2 diabetes. Common reasons for misdiagnosis are related to limitations in genetic testing. A precise molecular diagnosis is essential for the optimal treatment of patients and allows for early diagnosis of their asymptomatic family members. Objective. The aim of this study was to identify rare monogenic variants of common MODY genes in Japanese pediatric patients. Methods. We investigated 45 Japanese pediatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
3
3
0
Order By: Relevance
“…The cases group included 9 males and 11 females, this was in line with the findings of Katashima et al (13) in Japan, who enrolled 45 (17 males and 28 females) unrelated diabetic persons who were clinically diagnosed as cases of MODY. They investigated the presence of HNF4 and GCK genetic variants in juvenile study population with onset of DM before the age of seventeen years old.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The cases group included 9 males and 11 females, this was in line with the findings of Katashima et al (13) in Japan, who enrolled 45 (17 males and 28 females) unrelated diabetic persons who were clinically diagnosed as cases of MODY. They investigated the presence of HNF4 and GCK genetic variants in juvenile study population with onset of DM before the age of seventeen years old.…”
Section: Resultssupporting
confidence: 68%
“…In the current study, the mean age was 13.63±2.74 years, this was in the same way with Al-Kandari et al, (15), who conducted research on mutations among patients diagnosed with MODY in a nation where DM is an epidemic disease. Similarly, in the study by Katashima et al (13), the mean age at the time of diagnosis was 10.5±3.3 years. In contrast to Trhanint et al (14), who noted that the individuals' ages ranged anywhere from 13 to 19 years on average (range: 5-31 years old).…”
Section: Resultssupporting
confidence: 54%
“…More than 600 GCK mutations have been reported that distributed throughout the gene, [27] but only some of them have been identified by functional studies, most of them have only been predicted by online software without experimental verification. [28][29][30][31][32] In addition, most previous studies identified pathogenic mutations in GCK by functional analysis in which enzyme kinetics and thermal stability were most commonly used as evaluation standard. [33][34][35] Analysis of enzyme kinetics and thermal stability of mutant GCK can directly reveal the function of mutant GCK, but the experiment was rather complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that people with monogenic diabetes are often misdiagnosed as type 1 diabetes or type 2 diabetes 19 . Given the currently prohibitive cost and low yield of universal genetic testing in the vast majority with clinically classified type 1 and type 2 diabetes 14,[20][21][22] , there is therefore a need for more knowledge on who to test for monogenic diabetes using various clinical and biomarker based criteria that increase the yield for this diagnosis, thereby, making such genetic testing more cost-effective.…”
Section: Introductionmentioning
confidence: 99%